2004
DOI: 10.1038/sj.bjp.0705959
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for P2Y1, P2Y2, P2Y6 and atypical UTP‐sensitive receptors coupled to rises in intracellular calcium in mouse cultured superior cervical ganglion neurons and glia

Abstract: 1 P2Y receptors are expressed in the nervous system and are involved in calcium signalling in neurons and glia. In the superior cervical ganglion (SCG), RT-PCR analysis indicated the presence of P2Y 1,2&6 receptors. Rises in intracellular calcium in response to P2Y receptor stimulation were determined from adult mouse cultured SCG neurons and glia. 2 ADP evoked suramin (100 mM)-and pyridoxalphosphate-6-azophenyl-2 0 ,4 0 -disulphonic acid (PPADS, 30 mM)-sensitive rises in intracellular calcium in B80% of SCG n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 29 publications
(54 reference statements)
2
24
0
1
Order By: Relevance
“…Additionally, P2Y 6 mRNA expression was not detected in any of the tissues examined via RT-PCR analysis. While murine P2Y 6 mRNA expression is known to occur in the trachea, neurons, colon, and gallbladder (64)(65)(66)(67), and functional studies have suggested that P2Y 6 -like receptors reside in the murine kidney and vasculature (68,69), our RT-PCR findings are consistent with the lack of evidence in the literature supporting P2Y 6 localization to the murine kidney, lung, and jejunum. P2Y 4 receptor mRNA expression was not detected via real-time RT-PCR analysis in the lung or the kidney tissues of the BalbC mice utilized in these experiments.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, P2Y 6 mRNA expression was not detected in any of the tissues examined via RT-PCR analysis. While murine P2Y 6 mRNA expression is known to occur in the trachea, neurons, colon, and gallbladder (64)(65)(66)(67), and functional studies have suggested that P2Y 6 -like receptors reside in the murine kidney and vasculature (68,69), our RT-PCR findings are consistent with the lack of evidence in the literature supporting P2Y 6 localization to the murine kidney, lung, and jejunum. P2Y 4 receptor mRNA expression was not detected via real-time RT-PCR analysis in the lung or the kidney tissues of the BalbC mice utilized in these experiments.…”
Section: Discussionsupporting
confidence: 81%
“…Altogether, these results may allow us to exclude even the involvement of P2Y 4 receptors in the contractile effects induced by UTP. Therefore, UTP contractile responses appear to be mediated by atypical UTP-sensitive receptors, resembling those described in the dorsal spinal astrocytes of rats [35] and in the superior cervical ganglion neurons of mice [36]. However, the pharmacological profile of UTP contractile responses is the same as UTPγS, which, as already underlined, is nominally a selective P2Y 2 / 4 receptors agonist.…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, SGCs can potentially regulate extracellular ATP concentration without directly releasing ATP. SGCs express enzymes for breaking down ATP (61,62) and its metabolites (63,64), which directly regulate neuronal excitability (46,65,66). Therefore, it is possible that Gq-GPCR activation in ganglionic SGCs modulates the concentration of extracellular ATP and in turn active neuronal P2YRs.…”
Section: Discussionmentioning
confidence: 99%
“…In sympathetic and parasympathetic ganglia, SGCs form envelopes around individual neurons and synapses (44), creating a distinct functional unit consisting of a single ganglionic neuron and surrounding SGCs (45). SGCs express receptors for neurotransmitters (46,47), potassium channels (48,49), and neurotransmitter transporters (50,51), suggesting active roles in controlling the chemical environment critical for neuronal activation. However, the ability of sympathetic SGCs to regulate ganglionic neuronal activity has never been directly tested, likely due to the inability to selectively activate SGCs without also activating neurons.…”
Section: Discussionmentioning
confidence: 99%